1996
DOI: 10.2307/3546054
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Stream Benthic Prey by Benthic vs Drift Feeding Predators: A Meta-Analysis

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..Wiley-Blackwell and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Oikos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 32 publications
1
115
0
Order By: Relevance
“…Our low mortality estimate for single drift events of G. pulex suggests that actively entering the drift is likely to be adaptive in a number of situations, from life-or-death situations such as avoidance of benthic predators (Dahl and Greenberg 1996;Lima 1998) to simple patch-search behaviors (Bohle 1978;Kohler 1984Kohler , 1985. Thus, on a short-term level, we can explain the use of drift for predator escape and foraging, but we also suggest that a long-term perspective allows for an explanation of diel variations in drift related to avoidance of drift-feeding fish (Flecker 1992;Forrester 1994) and adaptations to minimize accidental dislodgement from the streambed.…”
Section: Discussionmentioning
confidence: 99%
“…Our low mortality estimate for single drift events of G. pulex suggests that actively entering the drift is likely to be adaptive in a number of situations, from life-or-death situations such as avoidance of benthic predators (Dahl and Greenberg 1996;Lima 1998) to simple patch-search behaviors (Bohle 1978;Kohler 1984Kohler , 1985. Thus, on a short-term level, we can explain the use of drift for predator escape and foraging, but we also suggest that a long-term perspective allows for an explanation of diel variations in drift related to avoidance of drift-feeding fish (Flecker 1992;Forrester 1994) and adaptations to minimize accidental dislodgement from the streambed.…”
Section: Discussionmentioning
confidence: 99%
“…Vitousek (1990) mentioned that in freshwater systems, predators frequently forage selectively on certain prey types, whereas Townsend (2003) suggested that predation has important effects at individual, population, community and ecosystem levels. Thus, predation represents a strong selective force that shapes and determines the structure of populations at lower trophic levels (Peckarsky, 1982;Bechara et al, 1992), and can alter the abundance and composition of the prey community (Dahl and Greenberg, 1996). Moreover, if the interactions are of great magnitude, predators can also alter the abundance of resources at lower trophic levels indirectly via "trophic cascade" by reducing consumer abundance and the consumer's consumption of resources (Bro¨nmark et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…While it is known that predation may have localized effects on drift concentration (i.e., causes depletion immediately downstream of a fishes focal point; Hughes 1992; Hayes et al 2007), an implicit assumption of most drift-foraging models is that there are no active feedbacks from predation on drifting invertebrate behaviour or populations (i.e., drift-feeding is assumed to be donor-controlled). Several studies have failed to detect an effect of drift-feeding fish on the benthos (Allan 1982;Dahl and Greenberg 1996); however, there is some evidence that predation on drift may have top-down effects (Forrester 1994;Diehl et al 2000;Meissner and Muotka 2006), and the ability of trout to consume a significant fraction of benthic production is well documented (e.g., Huryn 1996). Incorporating a major feedback between predation and drift production (entry rates) could substantially alter current drift-foraging modelling approaches.…”
Section: Consequences Of Drift Variation For Energy Flux To Fishmentioning
confidence: 99%